Role of the Bradyrhizobium japonicum ntrC gene product in differential regulation of the glutamine synthetase II gene (glnII). - Martin, G B (1988)
We isolated the ntrC gene from Bradyrhizobium japonicum, the endosymbiont of soybean (Glycine max), and examined its role in regulating nitrogen assimilation. Two independent ntrC mutants were constructed by gene replacement techniques. One mutant was unable to produce NtrC protein, while the other constitutively produced a stable, truncated NtrC protein. Both ntrC mutants were unable to utilize potassium nitrate as a sole nitrogen source. In contrast to wild-type B. japonicum, the NtrC null mutant lacked glnII transcripts in aerobic, nitrogen-starved cultures. However, the truncated-NtrC mutant expressed glnII in both nitrogen-starved and nitrogen-excess cultures. Both mutants expressed glnII under oxygen-limited culture conditions and in symbiotic cells. These results suggest that nitrogen assimilation in B. japonicum is regulated in response to both nitrogen limitation and oxygen limitation and that separate regulatory networks exist in free-living and symbiotic cells.